2016
DOI: 10.1177/0907568216649672
|View full text |Cite
|
Sign up to set email alerts
|

‘If there’s no sustainability our future will get wrecked’: Exploring children’s perspectives of sustainability

Abstract: Education for Sustainability is an internationally recognised field of learning that is currently mandated as a cross-curriculum priority in the Australian curriculum. Empirical research into children’s views about sustainability, and how they develop sustainability knowledge, however, remains limited. This article focuses on research that investigated children’s perspectives of sustainability in Victoria, Australia. The children were recruited through the Sustainable School Expo where they delivered keynote p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…In other words, the values framework must foster and defend democratic citizenship values (respect for diversity, value democratic participation, respect the opinion of others, etc.) [8,32], while acknowledging and promoting collective values (respect for indigenous rights, value of the common goods, and respect for non-human-others) [20,26,33] and aesthetic values (to value cultural and environmental heritage at local and global levels).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the values framework must foster and defend democratic citizenship values (respect for diversity, value democratic participation, respect the opinion of others, etc.) [8,32], while acknowledging and promoting collective values (respect for indigenous rights, value of the common goods, and respect for non-human-others) [20,26,33] and aesthetic values (to value cultural and environmental heritage at local and global levels).…”
Section: Resultsmentioning
confidence: 99%
“…Even if play is usually related to outdoor experiences in ECE, not all outdoor activities involve playing as a method. Green [33,54], for instance, argues for free exploration within natural settings in order to develop sensory engagements with place. To strengthen children's environmental exploration and agency, she proposed "Sensory Tours", a method to research children's experiences in nature and to allow them to freely explore the environment.…”
Section: Outdoor Education As a Basis For Esd Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In supporting our student researchers in the development of their ideas about which methods to use, we explored with them the challenges related to undertaking research with young children. Green (2017) and Horgan (2017) note a growth in child participatory research over the last two decades and how children are now recognised as ‘actors in their own right who have diverse and often divergent opinions and views about their everyday life worlds’ (Green, 2017: 154). Punch (2002) provided useful insights into these challenges by questioning which methods suit children given their marginalised position in adult society, noting the importance of critically reflecting upon the advantages and disadvantages of ‘child-centred’ (Punch, 2002: 323) methods to avoid assumptions about what methods are more appropriate for children’s perceived competencies or lack of them.…”
Section: Literature Informing the Projectmentioning
confidence: 99%
“…When it comes to environmental concern and activism, research shows that climate issues have gained the attention of children (Ceplak, 2006; Green, 2017). Early studies found that activist groups might set up symbolic fences (Strandbu and Krange, 2003), reducing the inclusiveness of the movement.…”
Section: Research On Resistance Among Children and Youthmentioning
confidence: 99%